J11 Can Music Therapy Improve The Quality Of Life In Huntington's Disease?. (17th September 2014) - van Bruggen-Rufi, M; Roos, RAC; Achterberg, W; Vink, A
Abstract : Background: Since there is no cure for Huntington's disease (HD) yet the intention of all forms of treatment is to improve quality of life. All treatment must be individually tailored, as the symptoms and signs are different for each person and change over time. Music therapy (MT) recognises individual needs and can be adapted to meet them. The aim is to maintain function and provide opportunities for compensatory behaviour. In MT functional training can be combined with cognitive, emotional and communicative/relational approaches. Practice based evidence has shown that MT could be a suitable non-pharmacological intervention to improve quality of life in every stage. Aims: This will be the first randomised controlled trial (RCT) to study the efficacy of MT, to be executed in three different long care facilities in The Netherlands, specialised in HD. The aim is to determine whether MT can improve expressive and communicative skills, and if so, whether these improvements lead to behavioural change. Methods: Sixty patients will be included and randomised: the experimental MT and the control group. The basic principle is to challenge expressive and communicative skills. Results: The primary outcome measures are the Behaviour Observation Scale Huntington and the Problem Behaviour Assessment. Assessments will take place at baseline and will be repeated after session 8 and 16, and 3 months after the last intervention. Conclusions: Music therapy is promising for improving QOL in HD, but not evidence based. This study aims to test it's effectiveness in a RCT.